Modelling fire sale contagion across banks and non-banks - Caccioli, Fabio; Ferrara, Gerardo; Ramadiah, Amanah (Journal of Financial Stability, 2024)
We examine the impact of fire sales on the UK financial system through commonly held assets across different financial sectors. In particular, we model indirect contagion via fire sales across UK banks and non-banks subject to different types of constraints. We find that performing a stress simulation that does not account for common asset holdings across multiple sectors can severely underestimate the fire sale losses in the financial system. In addition, pro-rata liquidation strategy would result in a higher level of fire sale losses in the system as whole, but a waterfall strategy may produce a higher spillover effect for a passive institution (or a passive sector) that chooses not to promptly liquidate any of its assets during distress while other institutions decide to do so.